If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + -3) + 4 = 14 Reorder the terms: 2(-3 + y) + 4 = 14 (-3 * 2 + y * 2) + 4 = 14 (-6 + 2y) + 4 = 14 Reorder the terms: -6 + 4 + 2y = 14 Combine like terms: -6 + 4 = -2 -2 + 2y = 14 Solving -2 + 2y = 14 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2y = 14 + 2 Combine like terms: -2 + 2 = 0 0 + 2y = 14 + 2 2y = 14 + 2 Combine like terms: 14 + 2 = 16 2y = 16 Divide each side by '2'. y = 8 Simplifying y = 8
| 2(3y-4)=3(2y+1) | | 19-c=14 | | 0y-3=64 | | -10(-3z-1+10a)= | | 6x+1=46-3x | | b-8/-5=-5 | | an-2/4 | | 11p-1=6p+1 | | 4x-5(1+3x)=7 | | 2(3y+1)=6y-2 | | 8x+2=3x+7 | | (x+y-z)(x-y+z)=0 | | -6-7x+2-x= | | 16=4(9f+6) | | 3(t-5)-8t=-7 | | -8f=-9f+10 | | 3a+15-5a+3= | | -10-2(x-4)=3(x+6) | | x^4*(a*x^2-1)=0 | | 60+68=512 | | -6×8/16 | | 4x+17=107 | | 8t=10+9t | | -10+5y=40 | | 9+12i=13x+4yi | | 6+6r-2r=-r-6+2r | | 6a+9b=2 | | 9x-3=10-4x | | 5pqr(pq-qr)=0 | | 10x+13y=93 | | X^3+y=8 | | 4/9=8/x |